PESAN-PESAN DAKWAH DALAM BUDAYA BARZANJI PADA MASYARAKAT - Shelfi Ramadhanis; Irman Irman (KINEMA: Jurnal Komunikasi dan Penyiaran, 2025)
Based on the research findings, it was discovered that: (1) The messages in Barzanji, by Sheikh Jafar bin Husin Abdul Karim bin Muhammad Al-Barzanji, convey the teachings of da'wah, emphasizing the strengthening of faith through belief in Allah, angels, prophets, and love for Prophet Muhammad SAW. (2) The messages in Barzanji emphasize the importance of worship, such as prayer, almsgiving, and charity, which shape the character of a righteous Muslim. (3) The messages in Barzanji highlight the importance of emulating the noble character of Prophet Muhammad, such as honesty, patience, and compassion. (4) Barzanji activities promote social values like cooperation and kinship, fostering community solidarity.